Interpersonal Communication and Household Resilience: The Dynamics of Husband-Wife Interaction in the Digital Era - Mirwan Mirwan; Apriani Apriani; Fahmi Hasbi; Abd Rahman; Murdifin Murdifin (Journal of Public Representative and Society Provision, 2026)
This study aims to analyze the role of interpersonal communication in building marital resilience in married couples within the context of socio-cultural change in the digital era. This study employed a qualitative approach through a literature review, reviewing articles from reputable national and international journals published between 2023 and 2025. Data analysis was conducted thematically to identify patterns in the concepts of communication, conflict, and marital resilience. The results indicate that openness, empathy, dialogic communication, and emotional regulation are key elements in maintaining harmonious marital relationships. This study also indicates that work pressure and digital distractions contribute to a decrease in the intensity of face-to-face communication and a decrease in the quality of emotional closeness between partners. Conceptually, this study confirms that interpersonal communication in the household is a dynamic, reflective, and contextual social process. The implications of this study emphasize the importance of interpersonal communication for husbands and wives as a social process that shapes household resilience in the face of the dynamics of contemporary social change.